Pengaruh Orientasi Kewirausahaan, Inovasi Produk, Dan Keunggulan Bersaing Terhadap Kinerja Pemasaran Usaha Dodol Di Kota Padang Sidempuan - Fikriyah Husna Rambe; Eri Yanti Nasution (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
This study aims to determine the effect of entrepreneurial orientation, product innovation, and competitive advantage on the marketing performance of the dodol business in the city of Padang Sidempuan. The data used is primary data with a sample of 47 SMEs in the culinary sector in the city of Padang Sidempuan. This study uses a quantitative descriptive analysis approach. Based on the results of the analysis, it is explained that partially or simultaneously entrepreneurial orientation, product innovation, and competitive advantage affect the marketing performance of the dodol business in Padangsidimpuan City.